2001
DOI: 10.1086/654451
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Post-World War II U.S. Inflation Dynamics

Abstract: For postwar U.S. data, this paper uses Bayesian methods to account for the four sources of uncertainty in a random coefficients VAR for inflation, unemployment, and an interest rate. We use the model to assemble evidence about the evolution of measures of the persistence of inflation, prospective long-horizon forecasts (means) of inflation and unemployment, statistics for testing an approximation to the natural unemployment rate hypothesis, and a version of a Taylor rule. We relate these measures to stories th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
543
3
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 641 publications
(578 citation statements)
references
References 18 publications
30
543
3
2
Order By: Relevance
“…As in Rotemberg and Woodford (1997), and Amato and Laubach (2001b), we begin the sample in the first quarter of 1980 because several empirical studies have identified a significant change in monetary policy around that period (see, e.g., Clarida, Galí and Gertler, 2000;Boivin, 2001;Boivin and Giannoni, 2003;Cogley andSargent, 2001, 2002). 34…”
Section: The Effects Of Monetary Disturbancesmentioning
confidence: 99%
“…As in Rotemberg and Woodford (1997), and Amato and Laubach (2001b), we begin the sample in the first quarter of 1980 because several empirical studies have identified a significant change in monetary policy around that period (see, e.g., Clarida, Galí and Gertler, 2000;Boivin, 2001;Boivin and Giannoni, 2003;Cogley andSargent, 2001, 2002). 34…”
Section: The Effects Of Monetary Disturbancesmentioning
confidence: 99%
“…Specifically, following Orphanides and Williams (2005b), we posit that private agents engage in perpetual learning, that is, they reestimate their forecasting model using a constant-gain least squares algorithm that weights recent data more heavily than past data. (See Sargent, 1999;Cogley and Sargent, 2001;and Evans and Honkapohja, 2001 for related treatments of learning.) This approach to modeling learning allows for the possible presence of time variation in the economy, including the natural rates of interest and unemployment.…”
Section: Expectations and Simulation Methodsmentioning
confidence: 99%
“…In principle, these zero restrictions may help or hinder the forecasting performance of agents in the model. In practice, allowing agents to include 13 See also Sargent (1999), Cogley and Sargent (2001), Evans and Honkapohja (2001), Gaspar and Smets (2002), and Gaspar, Smets and Vestin (2006) Thus, by imposing this structure, we are likely erring on the side of understating the costs of learning on macroeconomic performance.…”
Section: Perpetual Learning With Least Squaresmentioning
confidence: 99%